MEMECYLON NERVOSUM (MELASTOMATACEAE), A NEW SPECIES FROM SOUTH INDIA - Vadhyar, R. G.; Benjamin, J. H. F.; Sujana, K. A. (Edinburgh Journal of Botany, 2020)
Memecylon nervosum Vadhyar, J.H.F.Benj. & Sujana, a new species of Melastomataceae from the Kanyakumari Wildlife Sanctuary, Western Ghats, India, is described and illustrated. It is compared with the closely allied Memecylon heyneanum Benth. and Memecylon jambosioides Wight.